Research on Reflective Practice in TESOL - Thomas S.C. Farrell (2017)
In this comprehensive and detailed analysis of recent research on encouraging reflective practices in TESOL, Farrell demonstrates how this practice has been embraced within TESOL and how it continues to impact the field. Examining a vast array of studies through his own framework for reflecting on practice, Farrell’s analysis comprises not only the intellectual and cognitive but also the spiritual, moral, and emotional aspects of reflection. Reflection questions at the end of each chapter provide a jumping-off point for researchers, scholars, and teachers to further consider and reflect on the future of the field. Providing a holistic picture of reflection, this book is an original compendium of essential research on philosophy and principles, instruments used in studies, and theory and practice.